Evaluation of 3-hydroxy fatty acids as a pH and temperature proxy in soils from temperate and tropical altitudinal gradients. (March 2019) - Huguet, Arnaud; Coffinet, Sarah; Roussel, Anthony; Gayraud, Félix; Anquetil, Christelle; Bergonzini, Laurent; Bonanomi, Giuliano; Williamson, David; Majule, Amos; Derenne, Sylvie
Highlights: 3-hydroxy fatty acids analysed in soils from two contrasting altitudinal transects. Distribution of 3-hydroxy fatty acids correlated with air temperature and soil pH. Promising pH and temperature proxies in terrestrial environments. Abstract: Three hydroxy (3-OH) fatty acids (FAs), containing 10 to 18 C and a hydroxyl group in third position are characteristic components of Gram-negative bacteria. These compounds were used previously to detect and quantify Gram-negative bacterial communities in various types of samples, from terrestrial, aquatic and atmospheric environments. The relative abundance of 3-OH FAs in soils was recently shown to vary with mean annual air temperature (MAAT) and pH in soils from Mt. Shennongjia (China). In the current study, the concentrations and abundances of 3-OH FAs were determined in soils from altitudinal transects under tropical and temperate climates: Mt. Rungwe (SW Tanzania) and Mt. Majella (Central Italy), respectively. The aim was to (i) examine and compare the distributions of 3-OH FAs in soils from different climatic zones and (ii) to investigate the potential of 3-OH FAs as temperature and pH proxies. When combined with previously published data, a moderate correlation (R 2 0.62) between the summed iso and anteiso to the total amount of normal 3-OH FAs (RIAN index) and pH was obtained. We show that Gram-negative bacteria respond in the same way to temperature variations in soils from different latitudes, with a relative increase of the anteiso to normal 3-OH FA ratios of the C15 and C17 compounds (RAN15 and RAN17 indices, respectively) with decreasing temperature. Nevertheless, the intercepts of the relationships between RAN15 and MAAT are mountain-dependent, suggesting that regional calibrations may be required to use RAN15 as a temperature proxy. In contrast with RAN15, the statistical similarity of the local relationships between RAN17 and MAAT leads to a combined calibration (R 2 0.60, residual mean error 5.1 °C) covering a wide range of temperature (ca. 0–25 °C). As 3-OH FAs seem well-preserved in sedimentary archives, this strengthens the potential of these compounds as a temperature and pH proxy for paleoreconstructions in terrestrial settings.